Rozłóż wielomian na czynniki, znajdują pierwiastek całkowity
W(x)= x^3+x^2-x+2


Odpowiedź :

Odpowiedź:

W(1) = 1 +1 - 1 + 2 =/= 0

W(-1) = -1 + 1 + 1 + 2 =/= 0

W(-2)= -8 + 4 + 2 + 2 = 0        =>       (x+2)

       x^2 - x + 1

x^3+x^2-x+2: (x+2) =  

-(x^3+2x^2)

0 - x^2 - x + 2

   -(-x^2 - 2x)

0  - 0    + x + 2

            - ( x + 2 )

0 -  0  + 0 + 0          

x^3+x^2-x+2 = (x+2)(x^2-x+1)          

x^2 - x + 1 = 0

Delta  b^2 - 4ac = (-1)^2 - 4 * 1 * 1 = - 3     = > brak miejsc zerowych

Pierwiastkiem jest tylko -2

Szczegółowe wyjaśnienie: